2019
DOI: 10.3389/fneur.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Higher Non-processed Red Meat Consumption Is Associated With a Reduced Risk of Central Nervous System Demyelination

Abstract: The evidence associating red meat consumption and risk of multiple sclerosis is inconclusive. We tested associations between red meat consumption and risk of a first clinical diagnosis of central nervous system demyelination (FCD), often presaging a diagnosis of multiple sclerosis. We used food frequency questionnaire data from the 2003–2006 Ausimmune Study, an incident, matched, case-control study examining environmental risk factors for FCD. We calculated non-processed and processed red meat density (g/1,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…The incidence of MS is increasing globally, with a suggested role for environmental risk factors, including low sun exposure, low vitamin D status, smoking and history of infectious mononucleosis (2). Poor diet may be a modifiable risk factor for MS onset; however, the evidence is inconclusive and many studies have assessed single foods or nutrients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), rather than dietary patterns. The latter captures information about total diet, including the interactions that may occur between food components (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of MS is increasing globally, with a suggested role for environmental risk factors, including low sun exposure, low vitamin D status, smoking and history of infectious mononucleosis (2). Poor diet may be a modifiable risk factor for MS onset; however, the evidence is inconclusive and many studies have assessed single foods or nutrients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), rather than dietary patterns. The latter captures information about total diet, including the interactions that may occur between food components (17).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the largest, most well-characterized samples of people with early MS worldwide. We previously found that higher intake of very long chain omega-3 PUFAs (VLCn3PUFAs) (12), higher unprocessed red meat consumption (16) and greater adherence to a healthy dietary pattern (15) were associated with reduced risk of FCD in the Ausimmune Study. To build on this evidence, we tested associations between a Mediterranean diet and risk of FCD using data from the Ausimmune Study.…”
Section: Introductionmentioning
confidence: 99%
“…13 Despite the absence of endogenously produced Neu5Gc, experimental studies in humans and in Cmah −/− mice revealed that dietary Neu5Gc can become incorporated into tissues in trace amounts, essentially making Neu5Gc a dietary "xeno-autoantigen", and transfer of Neu5Gc-specific polyclonal IgG antibodies to Cmah −/− mice fed with Neu5Gc was shown to promote systemic inflammation. [13][14][15][16] Based on the aforementioned studies, it has been proposed that anti-Neu5Gc antibodies may contribute to the development of various human chronic inflammatory diseases that are not seen in great apes, such as MS. 15,17,18 Although healthy diets have been associated with a reduced risk to develop MS, 19 studies investigating red meat consumption and risk of MS have been inconclusive so far, [20][21][22] and it is unknown whether and to which extend dietary Neu5Gc can be incorporated into tissues including the CNS. However, given the structural similarity between Neu5Gc and Neu5Ac and the large overlap of reactivities toward both carbohydrate epitopes in individual patients, systemically increased IgG responses to both terminal glycan structures in patients with MS might partly result from cross-reactive antibody species 23 : exposure to a dietary xenoantigen expressed in peripheral tissues could elicit immune reactivity to a self-antigen, reexpressed upon myelin injury in MS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The Ausimmune Study is one of the largest, most wellcharacterised samples of people with early MS worldwide. Previously, higher vitamin D status [16], higher VLCn3PUFA intakes (largely from fish, but also including small amounts from commonly-consumed meats, such as beef and ham) [17], a higher healthy dietary pattern score [9], and higher unprocessed red meat consumption [18] have been associated with reduced risk of FCD in the Ausimmune Study. We build on these studies by examining the associations between fish consumption and risk of FCD using data from the Ausimmune Study.…”
Section: Introductionmentioning
confidence: 99%